1988
DOI: 10.1111/j.1476-5381.1988.tb11483.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non‐steroidal anti‐inflammatory drugs on rat gastric mucosal leukotriene C4 and prostanoid release: relation to ethanol‐induced injury

Abstract: 1 The effects of oral and subcutaneous administration of the non-steroidal anti-inflammatory drugs sodium salicylate, aspirin and indomethacin on ex vivo gastric mucosal release of leukotriene C4 (LTC4) prostaglandin E2 (PGE2), 6-oxo-PGFl, and thromboxane B2 (TXB2) were investigated in rats under basal conditions as well as after challenge with ethanol. 2 Basal release of PGE2, 6-oxo-PGF 1. and TXB2 was inhibited by oral administration of aspirin (0.6-400 mg kg-1) and indomethacin (4 or 20 mg kg-1), but not by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…These data are similar to the findings of other authors who showed a relationship between ethanol-induced gastric mucosal damage in vivo and increase in mucosally-synthesize LTC4 with no change in 6-keto-PGFl~ [12,13]. Pretreatment of rats with graded doses of NDGA, CuNSN and CuC12 protects against gastric mucosal injury caused by ethanol.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These data are similar to the findings of other authors who showed a relationship between ethanol-induced gastric mucosal damage in vivo and increase in mucosally-synthesize LTC4 with no change in 6-keto-PGFl~ [12,13]. Pretreatment of rats with graded doses of NDGA, CuNSN and CuC12 protects against gastric mucosal injury caused by ethanol.…”
Section: Discussionsupporting
confidence: 94%
“…In rats, oral instillation of ethanol induces a concentration-dependent increase in the ex-vivo release of LTC4 from gastric mucosal parallel to the production of haemorrhagic mucosal lesions while prostaglandin formation is not significantly affected [12][13][14]. Inhibition of gastric LTC4 formation by compounds such as sodium salicylate [13], cysteamine [15], carbenoxolone, nordihydroguaiaretic acid (NDGA) [12], is accompanied by protection against ethanol-induced gastric mucosal injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol caused a concentration-dependent increase in the ex vivo or in vitro release of LTC4 from the rat gastric mucosa (Peskar et al, 1986; Boughton-Smith & Whittle, 1988a,b); prostaglandin formation was not significantly affected (Boughton-Smith & Whittle, 1988a;Peskar et al, 1988). Inhibition of gastric LTC4 formation by compounds such as sodium salicylate (Peskar et al, 1988), 16,16-dimethyl PGE2 (Boughton-Smith & Whittle, 1988a), cysteamine or diethyl maleate (Lange et al, 1987), carbenoxolone or nordihydroguaiaretic acid, protected the rat gastric mucosa against ethanol-induced damage (Peskar et al, 1986); again prostaglandin release was not significantly affected (Boughton-Smith & Whittle, 1988a;Peskar et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of gastric LTC4 formation by compounds such as sodium salicylate (Peskar et al, 1988), 16,16-dimethyl PGE2 (Boughton-Smith & Whittle, 1988a), cysteamine or diethyl maleate (Lange et al, 1987), carbenoxolone or nordihydroguaiaretic acid, protected the rat gastric mucosa against ethanol-induced damage (Peskar et al, 1986); again prostaglandin release was not significantly affected (Boughton-Smith & Whittle, 1988a;Peskar et al, 1988).…”
Section: Introductionmentioning
confidence: 99%